ANALISIS DAMPAK LALU LINTAS (ANDALALIN) D I KAWASAN SMA KATOLIK ST. GABRIEL DAN SMK ST. GABRIEL MAUMERE (STUDI KASUS : JLN. SOEKARNO-HATTA KAB. SIKKA) - Patrisius Wege; Alfrendo Satriawan Kabupung (Program Studi Teknik Sipil, 2022)
‒ This research focuses on knowing the traffic performance on Soekarno-Hatta Road due to the activities at SMA Katolik St. Gabriel and SMK St. Gabriel and SMK St. Gabriel Maumere and also to find out the impact of traffic from existing activities at SMA Katolik St. Gabriel and SMK St. Gabriel. In this research, the researcher used the Indonesian Highway Guidance (2014). The date needed in this research consisted of primary and secobdary data. In collecting the data, the researcher conducted a traffic survey on Soekrano-Hatta Road. For traffic impacts, the Soekarno-Hatta Road had Road service level D, showing a stable flow, speed can still be controlled, V/C was still tolerable, for the hypothesis , there was a significant impact between the number of teachers and the number of students on entry and exit of vehicles